Potensi yogurt kacang merah (Phaseolus vulgaris L) ditinjau dari sifat organoleptik, kandungan protein, lemak dan flavonoid - Putriningtyas, Natalia Desy; Wahyuningsih, Siti (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: Â Yogurt is one of fermented milk products. Yogurt can also be made from red beans milk (Phaseolus vulgaris L). Red beans milk has a better taste and flavor compared to the other legumes. Red beans are a good source of complex carbohydrates, protein, vitamin B, iron, calcium,phosphorus and also rich in fiber and flavonoids. Red beans yogurt is one of the innovations of fermented red beans products. Objective: This study was aimed to determine the differences of red beans yogurt on organoleptic properties, protein, lipid and flavonoid contents. Methods: The study was held in February- September 2017 at Microbiology Laboratory of Center for Food and Nutrition, Gadjah Mada University and Dietetic and Culinary Laboratory of Respati University, Yogyakarta. The study was experimental design using Completely Randomized research Design (CRD) with four treatments, each replicated two times. The formulation of yogurt were A (control from cow milk and 2% skim milk); B (red beans and 2% skim milk); C (red beans and skim milk with comparison 1:0.5); D (red beans and skim milk with comparison 1:1). Hedonic scale test form was used for measuring organoleptic properties, such as flavor, taste, texture, colour and overall organoleptic properties. Hedonic level was done by twenty semi trained panelist. The difference of organoleptic properties were analyzed by Kruskal-Wallis test and continued by Mann Whitney U test. Results: Flavor, color, taste,and texture and overall organoleptic properties between groups were significantly different; p=0.001 respectively. The protein, lipid and flavonoid content between groups were not significantly different; p= 0.083; 0.919; 0.083 respectively. Yogurt C was preferable with a ratio of skim milk to red beans of 1:0.5. The highest protein and fat content was found in yogurt D. The highest flavonoid was found in yogurt C.Â Conclusion: There were no differences in protein, lipid and flavonoid content but different in organoleptic properties.